Catalytic hydrogenation of olefins by a multifunctional molybdenum-sulfur complex - Minghui Xue; Zhiqiang Peng; Keyan Tao; Jiong Jia; Datong Song; Chen-Ho Tung; Wenguang Wang (Nature Communications, 2024)
Abstract Exploration of molybdenum complexes as homogeneous hydrogenation catalysts has garnered significant attention, but hydrogenation of unactivated olefins under mild conditions are scarce. Here, we report the synthesis of a molybdenum complex, [Cp*Mo(Ph2PC6H4S−CH = CH2)(Py)]+ (2), which exhibits intriguing reactivity toward C2H2 and H2 under ambient pressure. This vinylthioether complex showcases efficient catalytic activity in the hydrogenation of various aromatic and aliphatic alkenes, demonstrating a broad substrate scope without the need for any additives. The catalytic pathway involves an uncommon oxidative addition of H2 to the cationic Mo(II) center, resulting in a Mo(IV) dihydride intermediate. Moreover, complex 2 also shows catalytic activity toward C2H2, leading to the production of polyacetylene and the extension of the vinylthioether ligand into a pendant triene chain.